Interpretive Narratives Related to Hajj in Surat Al-Baqara from Verse 196 to Verse 198 in Al-Mustadrak on the Two Sahihs - Study and Analysis - (Islamic Sciences Journal, 2023)
This research aims to state hadiths on the condition of the two sheikhs or on the condition of one of them or authentic only, not on the condition of one of them, and none of the two sheikhs produced them in their authenticity, and to study their wedge and find out what is acceptable and what is rejected from them, in order to present a verified scientific material in a single reference that makes it easier for researchers to return to it and citing it, For that reason, I entitled my research entitled my research (the interpretive narratives related to Hajj in Surat Al-Baqarah from verse 196 to verse 198 in Al-Mustadrak on Al-Sahihain _study and analysis).